Drivers of exchange rate dynamics in selected CIS countries: evidence from a FAVAR analysis - Christian Dreger; Jarko Fidrmuc (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
We investigate the likely sources of exchange rate dynamics in selected CIS countries (Russia, Kazakhstan, Ukraine, Kyrgyzstan, Azerbaijan, and Moldova) over the past decade (1999-2008). The analysis is based on country VAR models augmented by a regional common factor structure (FAVAR model). The models include nominal exchange rates, the common factor of exchange rates in the CIS countries, and global drivers such as gold, oil and share prices. Global, regional and idiosyncratic shocks are identified in a standard Cholesky fashion. Based on the decomposition of the variance of forecast errors, their relevance for exchange rates is explored. As a quite robust finding, CIS exchange rates have become more vulnerable to global shocks towards the end of the sample.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: F31; C22; G15; 330; Exchange rates; CIS countries; financial crisis; FAVAR models; Wechselkurs; Volatilität; Schock; Finanzmarktkrise; GUS-Staaten